Fiscal effects of aid - Mark MacGillivray; Oliver Morrissey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
It is clear from the implications of growth theory that the impact of aid depends on how it affects savings, investment and government behaviour. In respect of low-income countries, which are the principal aid recipients and the economies for which the issue of the impact of aid on growth is most important, it is government that is most important. This paper presents a review of studies that address the impact of aid on government fiscal behaviour. In particular, the focus is on fungibility and fiscal response studies. We argue that fungibility studies have been granted too much attention; these are narrowly focussed on the composition of government spending, and are not sufficiently informative about fiscal behaviour. Fiscal response studies are of greater relevance, as they attempt to address the effects of aid on behaviour regarding total spending, tax revenue and borrowing. Results show that the effects are complex and varied, but that aid tends to be associated with government spending increases in excess of the value of the aid, and can also have effects on tax effort and borrowing.
Keywords: O23; O55; H56; 330; fiscal policy; aid; sub-Saharan Africa; Öffentliche Einnahmen; Öffentliche Ausgaben; Entwicklungshilfe; Theorie